FENOMENA PENYALAHGUNAAN KOMUNIKASI NON ANTARPRIBADI DALAM KASUS KRIMINAL PENCULIKAN ANAK DENGAN TINJAUAN : PENDEKATAN HUBUNGAN KOMUNIKASI PADA TINGKAT KULTURAL (STUDI KASUS PENCULIKAN ANAK PADA KELURAHAN TOBEK GODANG, KECAMATAN BINAWIDYA, RT.08 / RW 01, PEKANBARU) - Sartika, Sartika; S, Ermairel; Kurniadi, Debby; Jummaulana, Hari Jummaulana; Sohnata Wiznih, Feunnah (Ensiklopedia of Journal, 2024)
This research aims to determine the phenomena that occur in child abduction cases through a non-interpersonal communication relationship approach at the cultural level. The perspective of this research is seen from communication science studies, the events taken in the discussion of this research are phenomena that occurred in the Tobek Godang sub-district, Binawidya sub-district RT 008 RW 001 using data collection techniques through free interviews with 2 main sources who experienced 4 cases of child abduction. The results of this research are seen from the non-interpersonal communication relationship approach at the cultural level, divided into 3 approach criteria, namely the introductory stage, the cultural and sociological stage and the individual stage of communicating personally.Keyword : Non-Interpersonal Communication, Cultural, Child Abduction